Welding mask - Mokhtar, Norashima; Eusud, Nur Fatihah Shazwana; Othman, Siti Amira (Penerbit UTHM, 2020)
Welding and welding safety are nothing new for all of us because this welding have been known around since 1800’s.A welding mask is one of the most important pieces of the personal protection that an equipment for the welder on having it. This welding can be used for the mask or helmet. Choose a good mask or helmet can protect the eyes and skin for not only from the severe sparks but also protect from potentially vision on damaging an ultraviolet and infrared rays that can be emitted by the arc.